Your Financial Action Plan - Josephine Turner; Michael Gutter (EDIS)
Revised! FCS-5204, an 11-page illustrated lesson adapted for use in Florida by Josephine Turner and Michael Gutter, helps families create financial action plans that will enable them to make wise decisions about their future financial success. Published by the UF Department of Family Youth and Community Sciences, October 2009.